PENDUGAAN PARAMETER GENETIK BEBERAPA KARAKTER AGRONOMI CABAI F4 DAN EVALUASI DAYA HASILNYA MENGGUNAKAN RANCANGAN PERBESARAN (AUGMENTED DESIGN) - Muhamad Syukur; Sriani Sujiprihati; Asril Siregar (Universitas Lampung, 2010)
The objective of this research was to estimated heritability and variability of agronomic characters and yield evaluation on F4 generations of pepper. This research was conducted at Ciampea, Bogor. The experimental design used was arranged in Augmented Designs. Plant materials were 41 F4 genotypes and 2 check varieties. The result indicated that the character of plant height, dichotomus height, stem diameter, yield per plant, fruit per plant, fruit length, fruit diameter, and fruit flesh thickness had broad genetic variability and high broad-sense heritability. The character of time of flowering, time of harvest and fruit weight had narrow genetic variability and low to medium broad-sense heritability. There were 7 selected genotypes: CCA 5511-6-3, CCA 5511-6-2, CCA 5708-1-1, CCA 5520-2-1, CCA 5511-3-1, CCA 5511-8-3, and CCA 5511-2-1